Intelligibility and the philosophy of nothingness : - Nishida, Kitaro (Maruzen Co., 1958)
The essays which comprise these companion volume have been selected from the proceedings of the East-West Philosopher's conferences held during the past 15 years. Here are examinations by world authorities of the rich, varied, and complicated philosophies of these countries.